A DESCRIPTIVE STUDY ON TEACHING READING COMPREHENSION AT THE EIGHTH YEAR STUDENTS OF MTs MUHAMMADIYAH 6 KARANGANYAR - JAMALUDIN, MUSTHOFA (2010)
The research aims at observing the teaching of English especially reading comprehension at Madrasah Tsanawiyah Muhammadiyah. The research was conducted at MTsM 6 Karanganyar in 2009/2010. The problems of the study include the process of teaching reading comprehension and the technique for teaching reading comprehension. In this research, the data are derived from event, information, and document. There are three techniques in collecting data namely: observation, interview, and document analysis. The research uses descriptive qualitative method in analyzing data. From the research finding, the process of teaching reading comprehension in MTsM 6 Karanganyar consists of three steps, namely: opening, study session, and closing. The first is opening; the teacher greeted and checked the students attendance. The second is study session; the teacher uses the four steps they are: Building Knowledge of Field (BKOF), Modeling of Text (MOT), Joint Construction of Text (JCOT), and Independent Construction of Text (ICOT). The last is closing, the teacher closed the meeting. The technique of teaching reading comprehension is: Read and Look up (silent reading) and Reading aloud.